Foundations for a More Stable Global System - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group, discussed the global financial architecture and developing countries. A stable financial architecture cannot be achieved without the proper structural, institutional, social and human foundations needed to make a modern market economy work. He identified the elements that should guide the choices of national governments, and the work that international institutions can do to assist them, and partnerships and co-operation between institutions. These include, first, good governance, strong public institutions, and a system that fights corruption; second, strong legal and a justice system able to guarantee the execution of those laws; and third, a well-regulated financial superstructure. Our social agenda should begin with those elements at the very heart of ensuring an opportunity at all levels of society: a good health system and an education system available to boys and girls equally. The environment is a crucial element in our foundation. We must resist a one-size-fits-all approach. At the Bank we work toward a comprehensive development framework agreed with each partner country.